LITERATURE IS A TOOL FOR THE FORMATION OF LOYALTY AND FIDELITY IN YOUNG PEOPLE - M.Jamoliddinov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article shows the writer in education through the use of biographical, sociological, psychological techniques in the course of lessons on the life path of such creators as Hamid Olimjon, Zulfiya, Said Ahmad, Saida Zunnunova as an example of the characters featured in literature teaching and works